Zinc(II) and manganese(II) complexes with 1, 3-bis(1-allylbenzimidazol-2-yl)-2-oxapropane: synthesis, crystal structures, antioxidant activities and DNA-binding properties. Issue 23 (6th November 2020) - Wu, Yancong; Xia, Lixian; Zhang, Geng; Wu, Huilu; Qu, Yao; Zhao, Kun; Wang, Cong
Abstract: Two new zinc(II) and manganese(II) complexes with the ligand 1, 3-bis(1-allylbenzimidazol-2-yl)-2-oxopropane (aobb), with composition [Zn(aobb)2 ](pic)2 ·DMF·CH3 OH (1 ) and [Mn(aobb)(DMF)2 (H2 O)] (pic)2 (2 ) (pic = picrate; DMF = N, N -dimethylformamide), have been synthesized and characterized by elemental analysis, electrical conductivities, X-ray single-crystal diffraction, IR, and UV–vis spectra. Single-crystal X-ray revealed that Zn(II) and Mn(II) centers are both located in the six-coordinate distorted octahedral geometry. The DNA-binding modes of the ligand and the complexes were investigated by electronic absorption titration, competitive binding with ethidium bromide and viscosity measurements. The experimental evidence indicated the ligand and complexes interact with calf thymus DNA through intercalation. The binding strength follows the order 2  > 1  >  aobb. Additionally, 2 displays potential superoxide dismutase activity in vitro studies. Graphical Abstract: